Comprehensive Breastfeeding Education: An Integration to Support Successful Breastfeeding Practice - Rialike Burhan; Elvi Destariyani; Sri Yanniarti; Yuniarti Yuniarti; Suci Solihat (Universitas Airlangga, 2023)
Breast milk is the best food for newborns, but the coverage of exclusive breastfeeding worldwide is only 40% (WHO, 2018). Babies who are not breastfed more susceptible to infectious diseases. The incidence of infants suffering from recurrent infectious diseases will result in malnutrition. The success of exclusive breastfeeding is largely determined in the first week of birth period as a critical phase in breastfeeding, so it is necessary to support comprehensive breastfeeding. The purpose of this study was to determine the effect of comprehensive breastfeeding education on the success of breastfeeding postpartum mothers in the Midwifery Independent Practice in Bengkulu City. The method used in this study was a quantitative pre-experiment with a two-group pre-posttest approach. The sample was taken by non-probability sampling by accidental sampling, in total 30 respondents. The group that was given the intervention was in the form of education in classes for pregnant women using a comprehensive breastfeeding education book, while the comparison group was given book only. The research variables studied were breastfeeding success (knowledge, attitudes, and breastfeeding practices) and external variables (age, parity, education, early initiation of breastfeeding, and husband support). Analysis test using Wilcoxon and Mann Withney and Ancova. The results showed that there was a significant effect of comprehensive breastfeeding education on attitudes, knowledge of successful breastfeeding practices (p<0.05). The implications of this research can be used as a reference as a development effort to increase breastfeeding success.